Organizational Citizenship Behavior Reduction: The Role of Transformational Leadership, Job Satisfaction, Organizational Commitment, and Organizational Culture on Employees at The Java Heritage Hotel Purwokerto - Maharani, Adinda Safirah; Purnadi, Purnadi; Darmawan, Akhmad; Widyaningtyas, Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study attempts to ascertain the result of transformational leadership, job satisfaction, organizational commitment, and organizational culture on organizational citizenship behavior (OCB) in the Java Heritage Hotel employees of Purwokerto. The research method used in this research was all 143 employees of Java Heritage Purwokerto, and 143 employees used saturated sampling techniques. These results indicate transformational leadership, job satisfaction, and organizational commitment do not affect OCB. However organizational culture has a positive and significant influence on OCB. The anticipated outcomes of this investigation should offer benefits for the leaders and employees of the Java Heritage Hotel Purwokerto.